An accessory renal aneurysm in a patient with absent renal artery: a case report - Wan, Jianghong; Chen, Chu Wen; Chen, Guoxin; Huang, Bin (Frontiers in Cardiovascular Medicine, 2024)
Introduction This study reports a patient who developed a secondary renal artery aneurysm (RAA) after occlusion of the main renal artery. Methods A 25-year-old woman was hospitalized due to an enlarged renal artery aneurysm (RAA). Computed tomography angiography revealed a 2.2 mm left renal aneurysm and the absence of the left renal artery trunk, with collateral blood supply from the branch arteries of the aorta. The left kidney function remained normal, allowing successful aneurysm embolization. Three years after embolization, the patient's hypertension improved and became more manageable. Conclusion Compensation through other abdominal aorta branches after renal artery trunk occlusion is rare, and these branches may also lead to the development of aneurysms. Regular monitoring of these patients is essential.